Strongyloides stercoralis infection and long-term follow-up in a privately-owned dog from north-west of Italy - Cagnasso, Federica; Rambozzi, Luisa; Miniscalco, Barbara; Molinar Min, Anna Rita; Borella, Franca; Borrelli, Antonio; Gianella, Paola (Veterinaria Italiana, 2023)
Strongyloides stercoralis is a zoonotic parasite, infecting human, cats and dogs. The infection is typical of tropical and subtropical areas, while it is underestimated in temperate countries. In Europe, data from humans demonstrate a large variability of infection prevalence; while scarce literature is available for dogs, with most cases reported in kennel dogs from southern Italy. A privately owned 8-month-old French Bulldog was examined because of chronic cough, diarrhea, and poor body conditions. Radiography of the thorax revealed a diffuse bronchial pattern and abdominal ultrasound showed unspecific signs of inflammation. Cytological analysis of a rectal swab revealed the presence of larvae compatible with Strongyloides sp. A parasitic infection causing protein-losing enteropathy and bronchopneumonia was suspected and fenbendazole was administered with a poor clinical response. Fecal Baermann test revealed S. stercoralis rhabditiform larvae and thinshelled eggs. Clinical signs resolved progressively after two subcutaneous ivermectin administrations (off-label) given two weeks apart. Serial coprological controls scheduled in the following 6 months were negative for larvae and eggs. Fecal real-time PCR confirmed negative results 6 months after treatment. The authors describe for the first time a case of S. stercoralis infection in a privately-owned dog from north-west of Italy (Piedmont).